2015
DOI: 10.3906/vet-1503-66
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of the patellar reflex for localization of the site of a single level thoracolumbar disc herniation in dogs

Abstract: The patellar reflex was used in this study to determine the site of thoracolumbar spinal cord dysfunction (T3-L3 or L4-L6) as a result of disc herniation. The results of neurological examinations were compared with the findings of CT myelography. This study was conducted on 21 dogs, selected from a total of 26 dogs confirmed to have a single thoracolumbar lesion. Results revealed that the accuracy of the patellar reflex for lesion localization was 71.4%. The accuracy of the patellar reflex (normal or hyperrefl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
(31 reference statements)
0
6
1
Order By: Relevance
“…In contrast to the work of Abdelhakiem et al [18] and Forterre et al [20], the patients in our study were all healthy and thus represented a homogenous group with high prevalence of the category 'normal'. Therefore, one could assume that the IA when assessing a reliable reflex should be 100%, however, perfect agreement is highly unlikely in medical studies [14].…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…In contrast to the work of Abdelhakiem et al [18] and Forterre et al [20], the patients in our study were all healthy and thus represented a homogenous group with high prevalence of the category 'normal'. Therefore, one could assume that the IA when assessing a reliable reflex should be 100%, however, perfect agreement is highly unlikely in medical studies [14].…”
Section: Discussioncontrasting
confidence: 87%
“…They described the findings in dogs with confirmed lesions within the lower motor neuron reflex arc of the pelvic limb in which only 37.5% showed a reduced withdrawal reflex, and a reduced PTR was found only in 16.7%. Additionally, Abdelhakiem et al [18] found in their study no lower motor neuron lesion to the pelvic limbs in dogs with a reduced reflex-activity (PTR). However, in nearly 30% of cases, a reduced reflex answer was misdiagnosed by the examiner for a lesion within the lower motor neuron of the pelvic limbs.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Several studies report on the reliability of the clinical neurological examination with regard to localisation (neurolocalisation). [17][18][19][20][21][22] From those studies, it is clear that the neurolocalisation is not always entirely accurate and that lesions may be clinically 'silent' .…”
Section: Discussionmentioning
confidence: 99%